Faktor Yang Mempengaruhi Motivasi Belajar Peserta Didik Dan Rencana Pelayanan Konseling Behavioral Menggunakan Teknik Self Management di SMAN 1 Linggo Sari Baganti - Agiesty, Cornellya; Wira Nita, Rahma; Imelda Usman, Citra (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This research is motivated by the existence of obstacles to students' learning motivation at school. The purpose of the research is to identify: 1) Internal factors, 2) External factors that influence students' learning motivation, 3) Behavioral counseling service plans with self-management techniques to overcome obstacles to learning motivation. The method used is descriptive qualitative. Key informants in this study were ZNC, additional informants were, (EW) homeroom teacher, (HR) BK teacher and (NAP) peers. The instrument used an interview format. For data analysis techniques using data reduction, data presentation and conclusion drawing. The results of the study show: 1) Internal factors that influence students' learning motivation are physical conditions such as frequent daydreaming and lack of focus that interfere with learning concentration, interest in learning only arises when the teacher uses interesting media, positive perceptions of the importance of learning are not applied when learning, lack of acceptance from peers reduces self-confidence and motivation. 2) External factors that influence learning motivation are the lack of support from parents who are busy working, indifference from friends, and less than optimal attention from teachers, 3) Behavioral counseling service plans with self-management techniques are compiled from problem identification to help students regulate behavior independently and form adaptive responses in facing less supportive conditions. The results of this study are recommended to guidance and counseling teachers to be able to provide counseling services, especially self-management techniques with the following technical strategies: 1) self-monitoring, 2) stimulus control, 3) self-reward.